Development of a Competence and Character-Based PAI Curriculum: A Literature Review - Dinatul Aini; Santri Nurul Hinayah (Journal of Islamic Religious Studies, 2025)
The development of a competence and character-based curriculum in Islamic Education (PAI) is essential for fostering both academic skills and moral integrity in students. This literature review investigates the integration of competence-based and character-based frameworks in the PAI curriculum in Indonesia. It examines theoretical foundations, previous studies, and practical challenges while proposing a framework for further curriculum development. The research identifies that competence-based education, which focuses on knowledge and practical skills, can be harmonized with character-building approaches that emphasize ethical and moral values. However, challenges such as the lack of clear guidelines for character education, the imbalance between cognitive and moral development, and the difficulty in assessing character traits hinder the integration process. Despite these challenges, opportunities arise through Indonesia's ongoing curriculum reforms, such as the Kurikulum Merdeka, which offers a more flexible and holistic approach. The integration of these frameworks is expected to positively impact students’ academic performance and personal development, cultivating responsible, well-rounded individuals. This study contributes to the improvement of the PAI curriculum by suggesting practical recommendations for balancing competence and character education in Islamic schools.